High-Performance and Disruptive Computing in Remote Sensing: HDCRS-A new Working Group of the GRSS Earth Science Informatics Technical Committee [Technical Committees] - Cavallaro, Gabriele; Heras, Dora B.; Wu, Zebin; Maskey, Manil; Lopez, Sebastian; Gawron, Piotr; Coca, Mihai; Datcu, Mihai (IEEE geoscience and remote sensing magazine, 2022)
The High-Performance and Disruptive Computing in Remote Sensing (HDCRS) Working Group (WG) was recently established under the IEEE Geoscience and Remote Sensing Society (GRSS) Earth Science Informatics (ESI) Technical Committee to connect a community of interdisciplinary researchers in remote sensing (RS) who specialize in advanced computing technologies, parallel programming models, and scalable algorithms. HDCRS focuses on three major research topics in the context of RS: 1) supercomputing and distributed computing, 2) specialized hardware computing, and 3) quantum computing (QC). This article presents these computing technologies as they play a major role for the development of RS applications. The HDCRS disseminates information and knowledge through educational events and publication activities which will also be introduced in this article.